The Management of Medical Waste at Putri Hijau Level II Hospital Under The Decree of Health Minister Republic of Indonesia Number 1204/MENKES/SK/X/2004 - Melpi, Yori (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2018)
Medical waste is a waste directly generated by medical activities at hospitals that classified as harmful and poisonous wastes and potentially endanger the hospital community that requires a systematic and sustainable management process in accordance with the policy of waste management according to the decree of Health Minister Number 1204/Menkes/SK/X/ on Hospital Health Environmental Requirements. This research is a descriptive research with qualitative method approach which aims to know and analyze the type of waste contained and waste management method applied by Putri Hijau Level II Hospital, Medan. In addition, the research sample is all parts and installation units related to waste management at Putri Hijau Level II Hospital, Medan. The data is analized to describe the type of waste and waste management method at Putri Hijau Level II Hospital, Medan. The result of this research showed that the waste at Putri Hijau Level II Hospital Medan is medical and non medical waste with garbages, rubbish, radioactive waste and liquid waste. Moreover, the process of liquid waste management at Tk Putri Hijau Level II Hospital Medan is still using the decree of Health Minister Republic of Indonesia Number 1204/year 2004 while the SOP that has been made has not been legalized and socialized. For liquid waste, the volume of liquid waste was generated in the average of 38 m3/day. The implementation of liquid waste management policy was applied according to SOP restricted in the Policy of Health Minister Republic of Indonesia Number 1204/ Menkes/ SK/ X/ 2004 on Hospital Health Environmental Requirements.Keywords: medical waste management, hospital waste